2019
DOI: 10.1063/1.5081098
|View full text |Cite
|
Sign up to set email alerts
|

Centrality-based identification of important edges in complex networks

Abstract: Centrality is one of the most fundamental metrics in network science. Despite an abundance of methods for measuring centrality of individual vertices, there are by now only a few metrics to measure centrality of individual edges. We modify various, widely used centrality concepts for vertices to those for edges, in order to find which edges in a network are important between other pairs of vertices. Focusing on the importance of edges, we propose an edge-centrality-based network decomposition technique to iden… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 81 publications
(81 reference statements)
5
47
0
1
Order By: Relevance
“…Our study revealed that predictive nodes are not the most central nodes in an evolving epileptic network, but we cannot yet make a similar statement for predictive edges. Recent modifications of centrality concepts for nodes to those for edges 59 are expected to provide further insights into the role of network edges and nodes in ictogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that predictive nodes are not the most central nodes in an evolving epileptic network, but we cannot yet make a similar statement for predictive edges. Recent modifications of centrality concepts for nodes to those for edges 59 are expected to provide further insights into the role of network edges and nodes in ictogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that there is a high inter-individual variation in pre-seizure period duration, which the variation in prodromal symptom onset and duration seems to support 39 . Finally, the results of this study should be combined with those of similar studies focusing on edges rather than nodes 19 , which could be expanded to include novel edge centrality indices 40 . Previous studies have assessed whether predictive edges connect predictive nodes 14 , reporting that this occurs in a majority of cases.…”
Section: Discussionmentioning
confidence: 99%
“…An eigenvector centrality for edges can be developed by considering the line graph and its adjacency matrix A (e) [11]. In this setting, A (e) ∈ R m×m has A (e) e 1 ,e 2 = 0 if and only if e 1 ∈ E and e 2 ∈ E share at least one node.…”
Section: Eigenvector Centrality For Nodes and Edgesmentioning
confidence: 99%